2020
DOI: 10.3390/antiox9111059
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Mitigates AFB1-Induced Hepatic Toxicity by Triggering Cattle Antioxidant and Anti-inflammatory Pathways: A Whole Transcriptomic In Vitro Study

Abstract: Aflatoxin B1 (AFB1) toxicity in livestock and human beings is a major economic and health concern. Natural polyphenolic substances with antioxidant properties have proven to be effective in ameliorating AFB1-induced toxicity. Here we assessed the potential anti-AFB1 activity of curcumin (pure curcumin, C, and curcumin from Curcuma longa, CL) in a bovine fetal hepatocyte-derived cell line (BFH12). First, we measured viability of cells exposed to AFB1 in presence or absence of curcumin treatment. Then, we explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 126 publications
11
61
1
Order By: Relevance
“…The significant decrease in AFB1-induced cytotoxicity was crucial in demonstrating the positive impact of R in cattle, and confirmed the extraordinary potential of this natural extract. In BFH12 exposed to AFB1, curcuminoids were already proven to increase cell viability [21], but such an effect was lower compared to that observed in the present study. In agreement with this study, in BME-UV1 cells 5 µM R provided some protection against the cytotoxicity observed after 48 h of AFB1 exposure (96 nM), increasing cell viability from 40% up to 60% [26].…”
Section: Resveratrol Cytotoxicitycontrasting
confidence: 97%
See 1 more Smart Citation
“…The significant decrease in AFB1-induced cytotoxicity was crucial in demonstrating the positive impact of R in cattle, and confirmed the extraordinary potential of this natural extract. In BFH12 exposed to AFB1, curcuminoids were already proven to increase cell viability [21], but such an effect was lower compared to that observed in the present study. In agreement with this study, in BME-UV1 cells 5 µM R provided some protection against the cytotoxicity observed after 48 h of AFB1 exposure (96 nM), increasing cell viability from 40% up to 60% [26].…”
Section: Resveratrol Cytotoxicitycontrasting
confidence: 97%
“…[8]. Catalytic activity of CYP3A was measured using a Promega commercial kit (P450-Glo TM CYP3A4 assay with Luciferin-IPA), following the protocol detailed in [21]. Six independent cell culture experiments were performed in sextuplicate.…”
Section: Resveratrol Cytotoxicitymentioning
confidence: 99%
“…Regarding the in vitro studies, a recent work by Pauletto et al [ 93 ] on bovine hepatocytes reported a significant increase in MDA concentration in incubated cells with AFB1, while their transcriptional profile of antioxidant enzymes (CAT, SOD, GSH-Px) were not affected. Two comparable studies conducted in vitro in bovine mammary epithelia cells that were treated with DON (0.25 μg/mL) for 24 h showed an increase in the concentration of MDA while TAC and GSH portrayed a decrease [ 94 , 95 ].…”
Section: The Effect Of Mycotoxins On the Antioxidant Status Of Rummentioning
confidence: 99%
“…The incidence of AFM 1 in milk is of concern, because milk is the main nutritional source for infants and children ( Conteçotto et al, 2021 ). AFM 1 in the milk is derived from the biotransformation of AFB 1 by the cow ( Barnes, 1970 ; Galvano et al, 1996 ; Pauletto et al, 2020 ). Since AFM 1 binds to the casein in the milk, it may be carried into high-content protein products such as cheeses, and this is worrying considering the highly consumption of cheeses by people of all ages ( Khaneghah et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%